Tatakelola Pemerintahan Berbasis Electronic Government di Kabupaten Semarang (Studi Kasus Dinas Kependudukan dan Pencatatan Sipil Kabupaten Semarang) - Firman Bimasakti; Yuwanto .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
Abstract. Electronic Government abbreviated e-Gov is the application of information and communication technology systems used and developed by the government in providing services to the community whenever and wherever people can get easy access to information and public services provided by the government. The essence of e-Gov implementation is to improve the quality of government services by utilizing information technology. The purpose of this study is to illustrate how the application of e-Gov in an effort to create Good Governance and to identify the support and obstruct factors e-Gov application in the Department of Population and Civil Registry of Semarang Regency.The research method using qualitative method with triangulation data that is observation, interview and data written or archive. Informants in this study are Head of Population Registration Services, Head of Civil Registration Services, Head of PIAK and Data Utilization and Head of Information Administration Division of Population Department of Population and Civil Registry of Semarang Regency.The results showed that the based governance of e-Gov in the Department of Population and Civil Registration of Semarang Regency is still classified in the Integration stage. Where the Department of Population and Civil Registration of Semarang Regency has been using a variety of digitalization services to support its tasks, but it can not be done optimally. There are 4 of 5 types of transformation points that can not be fulfilled, including services to the citizens to service by the citizens, traditional citizens to the online citizens, the digital divide to digital democracy and paper-based document to government online. There are three factors that obstruct the implementation of e-Gov in the Department of Population and Civil Registration of Semarang Regency, such as communication, resources and disposition. While the driving factor is the bureaucratic structure.Keyword : e-Gov, Department of Population and Civil Registration of Semarang Regency.